1994
DOI: 10.1523/jneurosci.14-10-06205.1994
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide degradation produces functional inactivation in the crustacean nervous system

Abstract: The pentapeptide proctolin (Proct.; Arg-Tyr-Leu-Pro-Thr) is a modulatory transmitter found throughout the crustacean nervous system. No information is available in this system, however, as to how the actions of this peptide are terminated. To study this issue in the crab Cancer borealis, we incubated exogenous proctolin (10(-5) M) with either the thoracic ganglion (TG) or with conditioned saline (CS) that had been preincubated with the TG. We removed aliquots at standard time points for analysis by reverse-pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Application of peptidase inhibitors strengthens the action of both bath applied and neuronally released peptides. Effects can also be seen in rhythmic network activity (Coleman et al 1994;Nusbaum 2002;Wood and Nusbaum 2002). Thus, it is suggestive that membrane bound peptidases play an important role in limiting the spread and temporal action of neuropeptides in the neuropil of a ganglion.…”
Section: Patterns Of Neuropeptide and Receptor Distribution In Drosopmentioning
confidence: 97%
See 1 more Smart Citation
“…Application of peptidase inhibitors strengthens the action of both bath applied and neuronally released peptides. Effects can also be seen in rhythmic network activity (Coleman et al 1994;Nusbaum 2002;Wood and Nusbaum 2002). Thus, it is suggestive that membrane bound peptidases play an important role in limiting the spread and temporal action of neuropeptides in the neuropil of a ganglion.…”
Section: Patterns Of Neuropeptide and Receptor Distribution In Drosopmentioning
confidence: 97%
“…One cell body is indicated (cb). a-d, g Are previously unpublished, e is from Skaer et al (2002)and f is from Nässel (2002) (STG) of a crab by application of peptidase inhibitors (Coleman et al 1994;Nusbaum 2002;Stein et al 2007). Specific blocking of peptidases known to inactivate either crab tachykinin or proctolin produces dramatic effects on network activity in the STG.…”
Section: Patterns Of Neuropeptide and Receptor Distribution In Drosopmentioning
confidence: 99%
“…Direct evidence in support of a functional role for an aminopeptidase in affecting the output of proctolinergic neurons has been obtained by studying the effect of aminopeptidase inhibitors on the actions of proctolin in the modulation of the pyloric rhythm by the stomatogastric nervous system in the crab, C. borealis (Coleman et al 1994;Wood and Nusbaum 2002). Both an aminopeptidase and a DPP-3-like enzyme were identified as proctolin-inactivating peptidases in the CNS of C. borealis with the former peptidase dominating the metabolism.…”
Section: Proctolin Inactivationmentioning
confidence: 99%
“…The metabolism and inactivation of proctolin in insects and crustaceans has been studied in several laboratories, identifying several proctolin-degrading peptidases (Quistad et al 1984;Starratt and Steele 1984;Isaac 1987;Puiroux and Loughton 1992;Coleman et al 1994). These enzymes were, however, not characterised at the molecular level and their precise identity remained unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that the peptidase activity for degrading both neuropeptides and hormonal peptides may be bound to the surface of the target tissues in arthropods (Rayne and O'Shea, 1992;Coleman et al, 1994;Li et al, 1997). Thus, we tested the duration of the myostimulatory response of LemTRP-1 and the blowfly peptide CavTK-I on the L. maderae hindgut when applied with and without peptidase inhibitors.…”
Section: Test Of Bioactivity Of Peptide Fragmentsmentioning
confidence: 99%